Synthesis of all‐carbon disubstituted bicyclo[1.1.1]pentanes by iron‐catalyzed Kumada cross‐coupling - Nugent, J; Shire, B; Caputo, DFJ; Pickford, HD; Nightingale, F; Houlsby, I; Mousseau, J; Anderson, EA (Wiley, 2020)
1,3‐Disubstituted bicyclo[1.1.1]pentanes (BCPs) are important motifs in drug design as surrogates for p‐substituted arenes and alkynes. Access to all‐carbon disubstituted BCPs via cross coupling has to date been limited to use of the BCP as the organometallic component, which restricts scope due to the harsh conditions typically required for the synthesis of metallated BCPs. Here we report a general method to access 1,3‐C‐disubstituted BCPs from 1‐iodo‐bicyclo[1.1.1]pentanes (iodo‐BCPs) by direct iron‐catalyzed cross‐coupling with aryl and heteroaryl Grignard reagents. This chemistry represents the first general use of iodo‐BCPs as electrophiles in cross‐coupling, and the first Kumada coupling of tertiary iodides. Benefiting from short reaction times, mild conditions, and broad scope of the coupling partners, it enables the synthesis of a wide range of 1,3‐C‐disubstituted BCPs including various drug analogues.